2024
DOI: 10.1186/s12877-023-04650-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-and lipid-related indices as a risk factor of hypertension in mid-aged and elderly Chinese: a cross-sectional study

Jiaofeng Gui,
Yuqing Li,
Haiyang Liu
et al.

Abstract: Objective Hypertension refers to the persistent elevation of blood pressure above the established normal range, resulting in increased pressure exerted by blood on the walls of blood vessels during its circulation. Recent studies have identified significant associations between obesity and lipid-related indices, as well as hypertension. Nevertheless, these studies have yet to comprehensively examine the correlation between the two variables. Our objective is to identify the fat and lipid-relate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Recent studies have shown that visceral adipose tissue (VAT) is more strongly associated with the development of hypertension than subcutaneous abdominal adipose tissue ( 23 , 24 ), The CVAI index has emerged as a straightforward and reliable indicator of visceral adiposity in Chinese individuals and is gaining attention due to its association with hypertension. In comparison with waist-to-hip ratio, BMI, and lipid accumulation product (LAP), the CVAI has demonstrated greater accuracy in assessing visceral adiposity in Chinese populations ( 13 , 25 , 26 ). A cross-sectional study involving 9,488 Chinese participants, which compared the predictive value of CVAI with other obesity indices including BMI, WC, VAI, LAP, waist-to-height ratio, body shape index, and body roundness index, revealed that the CVAI was the most reliable predictor of hypertension incidence ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that visceral adipose tissue (VAT) is more strongly associated with the development of hypertension than subcutaneous abdominal adipose tissue ( 23 , 24 ), The CVAI index has emerged as a straightforward and reliable indicator of visceral adiposity in Chinese individuals and is gaining attention due to its association with hypertension. In comparison with waist-to-hip ratio, BMI, and lipid accumulation product (LAP), the CVAI has demonstrated greater accuracy in assessing visceral adiposity in Chinese populations ( 13 , 25 , 26 ). A cross-sectional study involving 9,488 Chinese participants, which compared the predictive value of CVAI with other obesity indices including BMI, WC, VAI, LAP, waist-to-height ratio, body shape index, and body roundness index, revealed that the CVAI was the most reliable predictor of hypertension incidence ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with waist-to-hip ratio, BMI, and lipid accumulation product (LAP), the CVAI has demonstrated greater accuracy in assessing visceral adiposity in Chinese populations ( 13 , 25 , 26 ). A cross-sectional study involving 9,488 Chinese participants, which compared the predictive value of CVAI with other obesity indices including BMI, WC, VAI, LAP, waist-to-height ratio, body shape index, and body roundness index, revealed that the CVAI was the most reliable predictor of hypertension incidence ( 25 ). Additionally, Han and colleagues found that the CVAI exhibited superior predictive performance for hypertension among 9,359 rural residents in the Henan Province of China ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we collected thyroid function indices (especially TSH, free triiodothyronine (FT 3 ), and free tetraiodothyronine (FT 4 ) levels) from our patients. Considering the influence of other metabolic indicators on lipids, we also collected other clinical indicators such as body mass index (BMI) [ 24 ], waist circumference (WC) [ 25 ], and blood pressure level [ 26 ] (specifically, systolic blood pressure, SBP; diastolic blood pressure, DBP).…”
Section: Methodsmentioning
confidence: 99%
“…Povećana proizvodnja reaktivnih kiseoničkih radikala u mitohondrijama nastaje u uslovima povećane koncentracije glukoze i masnih kiselina u adipocitima, čija povećana količina dovodi do izmena u redoks potencijalu sekretornih puteva i utiče na koncentraciju i sekreciju pojedinih adipokina. Samo oslobađanje reaktivnih radikala iz masnog tkiva u krvotok remeti sekreciju insulina u pankreasu i učestvuje u patogenezi ateroskleroze i hipertenzije (48). Pokazano je da je stanje gojaznosti povezano sa nastankom niske hronične sistemske inflamacije u masnom tkivu (32,49).…”
Section: Gojaznost I Oksidativni Stresunclassified